1992
DOI: 10.1007/bf02245301
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic function and late luteal phase dysphoric disorder

Abstract: Thirty-eight subjects who met criteria for the DSM-III-R diagnosis late luteal phase dysphoric disorder (LLPDD) were compared with 18 controls in 5-HT uptake kinetics of the platelets in the premenstrual (day 26) as well as in the postmenstrual phase (day 4) of the cycle. Furthermore, 5-hydroxytryptophan (5-HTP) was administered to LLPDD patients and controls in both phases of the cycle, to investigate pituitary sensitivity for serotonin. Plasma samples for the measurement of cortisol and beta-endorphin were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A few studies have compared pain perception in dysmenorrheic and nondysmenorrheic females with mixed results,19-22 but we are aware of only one previous study comparing pain responses in PDD and non-PDD females. Kuczmierczyk and Adams23 evaluated mechanical pain responses in women with and without premenstrual syndrome (PMS) during the intermenstrual (days [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and premenstrual (days [24][25][26][27][28] phases of the menstrual cycle. The authors found no group or cycle-phase effects on pain threshold or tolerance, but PMS subjects reported higher pain intensity ratings during both phases.…”
mentioning
confidence: 99%
“…A few studies have compared pain perception in dysmenorrheic and nondysmenorrheic females with mixed results,19-22 but we are aware of only one previous study comparing pain responses in PDD and non-PDD females. Kuczmierczyk and Adams23 evaluated mechanical pain responses in women with and without premenstrual syndrome (PMS) during the intermenstrual (days [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and premenstrual (days [24][25][26][27][28] phases of the menstrual cycle. The authors found no group or cycle-phase effects on pain threshold or tolerance, but PMS subjects reported higher pain intensity ratings during both phases.…”
mentioning
confidence: 99%
“…In any case, at the moment, the concept of PMS may widely cover heterogeneous pathologies, which include women with PMS without PMDD, women with PMDD, and so on. As the previous studies (Bancroft et al 1991;Veeninga and Westenberg 1992;Yatham 1993;Bancroft and Cook 1995;Su et al 1997;Fitzgerald et al 1997;Steiner et al 1999;Rasgon et al 2000) probably dealt with these diseases together, some discrepancy probably occurred among their findings, which might depend on the ratio of PMDD and PMS without PMDD included.…”
Section: Discussionmentioning
confidence: 90%
“…With regard to neuroendocrine challenge tests to investigate central serotonergic function, Bancroft et al (1991) showed that growth hormone and cortisol responses to L-tryptophan infusion were significantly lower in women with premenstrual depression than controls both premenstrually and postmenstrually. Veeninga and Westenberg (1992) reported that cortisol responses to 5-hydroxytryptophan were not different between women with LLPDD and controls either premenstrually or postmenstrually. Yatham (1993) demonstrated a significantly blunted response to buspirone in women with LLPDD than healthy controls during follicular phase.…”
Section: Introductionmentioning
confidence: 92%
“…Premenstrual fluctuations in complaints were prospectively confirmed with a Dutch adaptation of the Menstrual Distress Questionnaire (MDQ; Moos, 1985;Van der Ploeg, 1986) on the 4th, 12th, 22nd and 26th days of the menstrual cycle for two consecutive cycles. A detailed description of the selection procedure and PMS criteria is reported elsewhere (Veeninga and Westenberg, 1992). Three hundred and eighty-four subjects were selected from the women who responded to the newspaper advertisement.…”
Section: Patientsmentioning
confidence: 99%
“…The absence of premenstrual fluctuations in complaints was prospectively confirmed with a Dutch adaptation of the Menstrual Distress Questionnaire (MDQ; Moos, 1985;Van der Ploeg, 1986) on the 4th, 12th, 22nd and 26th days of the menstrual cycle for two consecutive cycles. None of the controls fulfilled criteria for PMS (Veeninga and Westenberg, 1992). Ovulation detection was performed by sonography on the 12th and the 22nd day of two cycles.…”
Section: Controlsmentioning
confidence: 99%